Correlates and perceived risk of harm from tobacco products use in brunei darussalam: A secondary analysis of adult tobacco survey - Ogechukwu, Emmanuel Okondu; Hjh Norhayati Hj Md Kassim; Siti Khadizah Fakhriah Binti Hj Bakri; Mardiah Hj Mahmud; Okondu Chinedu Worlu (Student's Journal of Health Research, 2022)
Background: Smoking is a modifiable risk factor for cancer and heart disease, and it has been related to a shorter life expectancy in people who continue to smoke. Aim: We measured the perceived risk of harm from tobacco product use and predicted factors among adult Bruneians.  Methodology: A secondary analysis of the 1295 adult population using a record of adult tobacco survey conducted in December 2014- January 2015 in Brunei Darussalam Results: Out of the 92% of respondents who do not consider a smoke-free environment as important or not at all important, only 13.7% of them were smokers. Of the 89% of respondents with a good perceived risk of harm from tobacco product use, 12.8% of them were smokers and 76.1% were non-smokers, and 87.4% of respondents with good knowledge of tobacco health-related issues, 12.2% were current tobacco smokers against 75% non- smokers.  Conclusion:  The age of respondents and their level of education was associated with the perceived risk of harm.  Recommendation:  A regulatory system is needed in reducing exposure to tobacco smoke.